Remoción de tejidos enfermos y la aplicación de Trichoderma sp, para el control de Moniliasis (moniliophthora roreri cif. & par) y Escoba de bruja (crinipellis perniciosa (stahel singer) del Cacao (theobroma cacao l.) en Tarapoto- San Martín - Bernales García, Richard Keneth (2001)
The effect of Thichoderma Sp (TR-6), it's from Tingo María, Huánuco and the Remosión semimonthly of sick tissues far the control of the moniliasis (mo) broom of witch (Eb) and dark grey rotión (Pp) of the cocoa, it was verified in an experimental parcel of land in the town of Cachiyacu, Tarapoto, San Martln, the treatments used, they were: TO= without Remosión of fruits and without TR-6; T1 = with Remosión and with TR-6: T2 = with Remosión and without TR-6: T3 = without Remosión and with TR-6; distributed under the design complet forest to the chance with three repetitions. Each parcel of !and was constituted for fifteen plants. The applications of TR-6 were rea!ized each month in a total of four applications, starting to the moment of the maximum flowering between the months from December to March. During one year registered the number of health frits and sick fruits for MO, Eb, the dates obtained they were processing far obtain the incidence of sick fruits, valuation of increase of the sickness, area under the curve of progress of the sickness (ADCPE) and output. The analysis of the progress of the sickness was realized under the design of Regression Monomolecular. The incidence of sick fruits was less in the treatment T1 and was high in TO, 15.2 and 66.5 % respectively. Mo more frequent in T0, while in the other treatments predominated the presence of Eb. There weren't affected fruits far Pp. The reduction of the incidence of sick fruits by effect of the applications of TR-6 was 3.1 % while that this reduction is higher when mixes with the remosion (14.4 %). The remosion only reduced 36.9 % the incidence of sick fruits. According the reduction of the incidence of brooms totals to level of buds watch a similar effect of the sick fruits, there weren't found significant effect with the application of TR-6 (0.9 %), while in the combination with remosion this effect was higher (5.7 %) if by only the remosion of sick tissue decreased in 30.7 % and the incidence of vegetative brooms. In all the cases the valuation of decrease of the sickness so like the ADCPE, are directly proportions to the incidences found. The outputs in dry cocoa were inversely proportions to the incidence of the sickness in all the treatments.